Non‐geostationary satellite orbit communications satellite constellations history. (27th August 2020) - Butash, Tom; Garland, Peter; Evans, Barry
Summary: This special issue of the journal on 'constellations' comes at a critical time in their development as a second wave of such non‐geostationary satellite orbit (NGSO) systems is being planned and deployed. These mega‐constellations as they have become known are, with a few exceptions, very much larger than those in the first wave and are focused on broadband and 5G applications rather than speech and narrow band data as those deployed in the first wave during the 1990s. However, as we explain in this editorial, there are many similarities in the design and business plans to the first wave and, perhaps, many similar lessons to be learned.